Continuous low-dose cyclophosphamide plus prednisone in the treatment of relapsed and refractory multiple myeloma with severe complications - Shi, Haotian; Wei, Wei; Peng, Rong; Chen, Haimin; Zhou, Nian; Wu, Lixia; Yu, Wenjun; Zhao, Wenhao; Hou, Jian; Zhou, Fan (Frontiers in Oncology, 2023)
Background/objective: We retrospectively analyzed the effective and safety of continuous low-dose cyclophosphamide combined with prednisone (CP) in relapsed and refractory multiple myeloma (RRMM) patients with severe complications. Methods: A total of 130 RRMM patients with severe complications were enrolled in this study, among which 41 patients were further given bortezomib, lenalidomide, thalidomide or ixazomib on the basis of CP regimen (CP+X group). The response to therapy, adverse events (AEs), overall survival (OS) and progression-free survival (PFS) were recorded. Results: Among the 130 patients, 128 patients received therapeutic response assessment, with a complete remission rate (CRR) and objective response rate (ORR) of 4.7% and 58.6%, respectively. The median OS and PFS time were (38.0±3.6) and (22.9±5.2) months, respectively. The most common AEs were hyperglycemia (7.7%), pneumonia (6.2%) and Cushing’s syndrome (5.4%). In addition, we found the pro-BNP/BNP level was obviously decreased while the LVEF (left ventricular ejection fraction) was increased in RRMM patients following CP treatment as compared with those before treatment. Furthermore, CP+X regimen further improved the CRR compared with that before receiving the CP+X regimen (24.4% vs. 2.4%, P=0.007). Also, both the OS and PFS rates were significantly elevated in patients received CP+X regimen following CP regimen as compared with the patients received CP regimen only. Conclusion: This study demonstrates the metronomic chemotherapy regimen of CP is effective to RRMM patients with severe complications.